Ioannis Kolettis. The Vlach from the ruling elite of Greece - Minov, Nikola; Jovanovski, Dalibor (My University, 2017)
The article is aimed to show how Ioannis Kolettis, the first Vlach to become Prime Minister of the Greek kingdom. The Vlach people, despite being a stateless ethnic minority in southeastern Europe, have traditionally been deeply involved in every part of the social life in the countries they inhabited. In Greece, more than in any other country, the influence of certain prominent Vlachs has been felt since the foundation of the modern Greek state. Ioannis Kolettis, who served as Prime Minister of Greece from 1844 to 1847, is a striking example of the above thesis. I. Kolettis left a lasting impression on Greek internal and foreign affairs. Despite his non-Greek but Vlach origins, I. Kolettis is credited for conceiving the Great Idea, which became the core of Greek foreign policy and dominated Greek domestic politics for over half a century.
Keywords: Kolettis, Greece, Vlachs, Great Idea, politics, Great Powers, Ottoman Empire